Refinement as ethics principle in animal research: Is it necessary to standardize the Environmental enrichment in laboratory animals? - FISCHER,MARTA L. (2021)
Abstract The Environmental enrichment technique, although scientifically recognized for raising the level of animal welfare, has led to the questioning of its influence on the results of experimental research. Thus, the goal is to promote reflection about the need for standardization of these procedures. For that, documents and experimental analysis were done, in order to quantify and characterize the types of environmental enrichment used and to evaluate the effect of that in the social behavior of Rattus norvegicus. Data from the document review confirmed the hypothesis that the researchers have used a variety of methods, not demonstrating a concern for standardization and prior assessment of its effects on the search results. Demand was corroborated in the experimental study in which, although there was available a simple object acting as refuge promotes behavioral improvements, the presence of the co-specific, as well as characteristics of the micro and macro environment can compromise the homogeneity of the sample. The data from this study endorse the need for validation procedures of environmental enrichment for specific proposals, to investigative data comparison, are possible and contribute to the refinement of the search to reduce the number of animals targeted for this purpose.